Pengalaman psikologis mahasiswa dalam menggunakan kecerdasan buatan (AI) pada penulisan akademik - muda, raditya ariesta (Maliki Interdisciplinary Journal, 2026)
This study aims to examine students’ psychological experiences in using artificial intelligence in academic writing. The rapid development of digital technology has transformed how students produce academic work, not only technically but also psychologically. This research employs a qualitative approach to explore students’ perceptions, experiences, and internal dynamics in depth. The findings indicate that the use of artificial intelligence provides positive impacts, including increased efficiency, reduced cognitive load, and ease in developing ideas. However, it also presents negative effects such as dependency, decreased self-confidence, and the potential decline of critical thinking skills. The study further reveals the presence of psychological conflict in the form of cognitive dissonance between efficiency demands and academic integrity. In addition, students’ self-efficacy and coping strategies play a crucial role in determining how technology is utilized. Therefore, the use of artificial intelligence in academic writing should be managed wisely and proportionally to support learning processes without hindering students’ psychological development.